2(x+4)(x+7)=(2x+1)(x-9)

Simple and best practice solution for 2(x+4)(x+7)=(2x+1)(x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+4)(x+7)=(2x+1)(x-9) equation:


Simplifying
2(x + 4)(x + 7) = (2x + 1)(x + -9)

Reorder the terms:
2(4 + x)(x + 7) = (2x + 1)(x + -9)

Reorder the terms:
2(4 + x)(7 + x) = (2x + 1)(x + -9)

Multiply (4 + x) * (7 + x)
2(4(7 + x) + x(7 + x)) = (2x + 1)(x + -9)
2((7 * 4 + x * 4) + x(7 + x)) = (2x + 1)(x + -9)
2((28 + 4x) + x(7 + x)) = (2x + 1)(x + -9)
2(28 + 4x + (7 * x + x * x)) = (2x + 1)(x + -9)
2(28 + 4x + (7x + x2)) = (2x + 1)(x + -9)

Combine like terms: 4x + 7x = 11x
2(28 + 11x + x2) = (2x + 1)(x + -9)
(28 * 2 + 11x * 2 + x2 * 2) = (2x + 1)(x + -9)
(56 + 22x + 2x2) = (2x + 1)(x + -9)

Reorder the terms:
56 + 22x + 2x2 = (1 + 2x)(x + -9)

Reorder the terms:
56 + 22x + 2x2 = (1 + 2x)(-9 + x)

Multiply (1 + 2x) * (-9 + x)
56 + 22x + 2x2 = (1(-9 + x) + 2x * (-9 + x))
56 + 22x + 2x2 = ((-9 * 1 + x * 1) + 2x * (-9 + x))
56 + 22x + 2x2 = ((-9 + 1x) + 2x * (-9 + x))
56 + 22x + 2x2 = (-9 + 1x + (-9 * 2x + x * 2x))
56 + 22x + 2x2 = (-9 + 1x + (-18x + 2x2))

Combine like terms: 1x + -18x = -17x
56 + 22x + 2x2 = (-9 + -17x + 2x2)

Add '-2x2' to each side of the equation.
56 + 22x + 2x2 + -2x2 = -9 + -17x + 2x2 + -2x2

Combine like terms: 2x2 + -2x2 = 0
56 + 22x + 0 = -9 + -17x + 2x2 + -2x2
56 + 22x = -9 + -17x + 2x2 + -2x2

Combine like terms: 2x2 + -2x2 = 0
56 + 22x = -9 + -17x + 0
56 + 22x = -9 + -17x

Solving
56 + 22x = -9 + -17x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '17x' to each side of the equation.
56 + 22x + 17x = -9 + -17x + 17x

Combine like terms: 22x + 17x = 39x
56 + 39x = -9 + -17x + 17x

Combine like terms: -17x + 17x = 0
56 + 39x = -9 + 0
56 + 39x = -9

Add '-56' to each side of the equation.
56 + -56 + 39x = -9 + -56

Combine like terms: 56 + -56 = 0
0 + 39x = -9 + -56
39x = -9 + -56

Combine like terms: -9 + -56 = -65
39x = -65

Divide each side by '39'.
x = -1.666666667

Simplifying
x = -1.666666667

See similar equations:

| 2x^3-22x^2+60x=0 | | x(7x+5)-x=0 | | -4-11=7x+15-6x | | .03x+18000=90 | | 4(a-4)=2(a+5) | | -15=r-8 | | 7+2(x-3)-4x= | | y+1(9+24)-28=96 | | 5x+20=5x-18 | | 10+a=26 | | x(7x+5)-x(x)(x)=0 | | 5x^2+10x+8y^2-48y+37=0 | | 2(113-2c)+4c=226 | | 20+10x-(8x-12)=68 | | .03x+.07(18000-x)=90 | | 4k-(-6)=-2-(-16)-(-2) | | 6n-.7=11 | | 10+n=25 | | -18x^2+51x+8=0 | | X^2+6x+64=48 | | 9x^4-64=0 | | 4c^2+7x-15=0 | | 15+n=6 | | 3x^4-7x^2=0 | | (4x+2)-x=(2x-10) | | 9(2+v)+35v=14v | | .5x(x+4)=16 | | 69=12 | | 2a+4b=226 | | 8(4+v)+34v=14v | | -2.3q+16=-5q-3 | | x^2+6x-24.01=0 |

Equations solver categories